ADVANCING RENAL EDUCATION: HYBRID SIMULATION, USING SIMULATED PATIENTS TO ENHANCE REALISM IN HAEMODIALYSIS EDUCATION. Issue 2 (29th January 2015) - Dunbar‐Reid, Kylie; Sinclair, Peter M.; Hudson, Denis
SUMMARY Background Simulation is a well‐established and proven teaching method, yet its use in renal education is not widely reported. Criticisms of simulation‐based teaching include limited realism and a lack of authentic patient interaction. Method This paper discusses the benefits and challenges of high‐fidelity simulation and suggests hybrid simulation as a complementary model to existing simulation programmes. Conclusion Through the use of a simulated patient, hybrid simulation can improve the authenticity of renal simulation‐based education while simultaneously teaching and assessing technologically enframed caring.